Theory into Practice: The KSU PDS Model - Sally J. Yahnke; M. Gail Shroyer (Educational Considerations, 2014)
The 1983 publication of A Nation at Risk: The Imperative for Educational Reform (National Commission of Excellence in Education) “initiated the longest sustained period of attention to public education in the nation’s history and ignited a new wave of interest in teacher preparation.”
Keywords: beliefs; purpose; vision; Partnership; responsibilities; roles; teachers; goals